1995
DOI: 10.1111/j.1432-1033.1995.tb20558.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Protease Processing Sites in a Multidomain Proteinase Inhibitor Precursor from Nicotiana Alata

Abstract: A gene encoding a 40.3-kDa serine proteinase inhibitor (PI) precursor is expressed at high levels in the stigma of the ornamental tobacco, Nicotiana alata. The precursor is processed proteolytically in vivo to release five homologous proteinase inhibitors of approximately 6 kDa, as well as two flanking peptides. The five PIs have been purified from stigmas and identified by N-terminal sequencing, electrospray mass spectrometry and inhibition activity against chymotrypsin or trypsin. One of the PIs inhibits chy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…This suggests that in No two domain expansion events occurred after speciation. The evolutionary advantages of repetitive TPI domain expansion have not been established, but it is reasonable to assume that repetitive domains provide plants with a more efficient use of transcription, translation, and cell-compartment targeting (Heath et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that in No two domain expansion events occurred after speciation. The evolutionary advantages of repetitive TPI domain expansion have not been established, but it is reasonable to assume that repetitive domains provide plants with a more efficient use of transcription, translation, and cell-compartment targeting (Heath et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that processing occurs after the protein has passed through the endomembrane system (Atkinson et al ., 1993). Cleavage may occur adjacent to the linker or between the asparagine and aspartic acid residues, with subsequent trimming by nonspecific endogenous peptidases (Heath et al ., 1993). N‐terminal amino acid sequencing confirmed the presence of residues 3–16 (inclusive) of GFP for the smaller Western‐positive protein expressed by BY2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the properties of IP-repeats and domains revealed that they had 5.2-5.7 kDa molecular weight. HEATH et al (1995) have shown that molecular weight of PI domains in N. alata is 6 kDa and sequence length is 53 amino acids. Domains had negative charge and only domain II was stable (Table 3).…”
Section: Results and Discussin Expression Levels Of Pi2mentioning
confidence: 99%